Continuous versus step by step training for learning surgical anatomy on an open inguinal hernia model - Tahmina Nazari; Muhammad H Zeb; Mary EW Dankbaar; Johan F Lange; Jeroen JG van Merrienboer; Theo Wiggers; David R Farley (Journal of Surgery and Surgical Research - Peertechz Publications, 2019)
Background: Segmentation of surgical procedures may facilitate learning. The step-by-step framework segments surgical procedures in a standardized manner based on anatomy. The effects of the framework are compared to a continuous approach, on learning anatomy on an inguinal hernia model by pre-novices.